Fungal diversity on Heritiera Littoralis dryand. ex W. Ait. - Ng, Kenneth O.
Mangroves are unique tropical and subtropical ecosystems comprising climax communities of trees and shrubs colonizing low lying coastal and estuarine areas. Its primary productivity is estimated to be 1 kg/msquared per annum and the biomass released in the form dead trees and small litter are available for colonization and degradation by mangrove fungi. Several studies on the occurrence of fungi have been done using randomly collected driftwood. However, very few studies have been done using specific mangrove hosts. This tudy aims to provide additional information on the host preference of mangrove fungi. Specifically, the objectives are: (1) To describe, identify and classify fungi collected on Heritiera littoralis in Barangay Plandico, Concepcion, Philippines; (2) to determine the abundance and frequency of occurrence (percent) of the identified fungi; and (3)to compare the mycota found in Heritiera littoralis with other mangrove hosts, which have been studied for host specificity., Direct examination of the 60 littoralis samples collected from Barangay Plandico, Concepcion, Iloilo yielded 21 species: 12 Ascomycota and 7 Deuteromycota and 2 unidentified species. The most frequently occuring species were Cirrenalia tropicalis (53.33 percent), Hypoxylon oceanicum (43.33 percent), Periconia prolifica (43.33 percent), Phoma spp. (36.67 percent), Tricholacdium achrasporum (36.67 percent), and Dactylospora haliotrepha (30 percent). Zalerion varium (20 percent), Hypoxylon nectriodeum cf. (16.67 percent), Savoryella lignicola (11.67 percent), Kallichroma tethys (10 percent), and Lignincola laevis (10 percent) occurered as frequent species (10-29 percent). The rest were classified as infrequent (<10 percent) species. More species of ascomycetes were collected but the deuteromycetes were more dominant in this study. This could be attributed to the late stage of decomposition of wood samples and prolonged incubation that encouraged anamorphic proliferation.